Artificial Heterointerfaces Achieve Delicate Reaction Kinetics towards Hydrogen Evolution and Hydrazine Oxidation Catalysis. (27th January 2021) - Qian, Qizhu; Zhang, Jihua; Li, Jianming; Li, Yapeng; Jin, Xu; Zhu, Yin; Liu, Yi; Li, Ziyun; El‐Harairy, Ahmed; Xiao, Chong; Zhang, Genqiang; Xie, Yi
Abstract: Electrochemical water splitting for H2 production is limited by the sluggish anode oxygen evolution reaction (OER), thus using hydrazine oxidation reaction (HzOR) to replace OER has received great attention. Here we report the hierarchical porous nanosheet arrays with abundant Ni3 N‐Co3 N heterointerfaces on Ni foam with superior hydrogen evolution reaction (HER) and HzOR activity, realizing working potentials of −43 and −88 mV for 10 mA cm −2, respectively, and achieving an industry‐level 1000 mA cm −2 at 200 mV for HzOR. The two‐electrode overall hydrazine splitting (OHzS) electrolyzer requires the cell voltages of 0.071 and 0.76 V for 10 and 400 mA cm −2, respectively. The H2 production powered by a direct hydrazine fuel cell (DHzFC) and a commercial solar cell are investigated to inspire future practical applications. DFT calculations decipher that heterointerfaces simultaneously optimize the hydrogen adsorption free energy (Δ G H* ) and promote the hydrazine dehydrogenation kinetics. This work provides a rationale for advanced bifunctional electrocatalysts, and propels the practical energy‐saving H2 generation techniques. Abstract : An efficient bifunctional electrocatalyst toward hydrazine‐assisted H2 production was designed by constructing the Ni3 N‐Co3 N heterointerfaces on Ni foam (Ni3 N‐Co3 N PNAs/NF). The catalyst can achieve energy‐saving hydrogen production in an overall hydrazine splitting (OHzS) unit, showing its potential for practical applications.